Holography-A Critical Debate within Contemporary Visual Culture - Pepper, Andrew (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Artists have been exploring the spatial, conceptual and three-dimensional qualities of holography for over fifty years. Why, then, is there so little sustained critical pressure placed on this process, methodology and mode of visualisation which underpins the developing practice?In 1994, pioneering British artist Margaret Benyon, in her doctoral thesis, posed the question "How is Holography Art", and offered a range of answers, by applying critical pressure to her considerable work in the field. Over 25 years later, we have used Benyon's investigation as an invitation to ask more questions. This Special Issue in Arts brings together artists working with holography, as well as curators and long-term expert observers with an interest in the medium, to open up a more comprehensive discussion. They have reflected on the development of their work and its place within a cultural and critical framework. The curators and observers have employed a wider lens from their standpoints outside the field, but this is located firmly within current cultural discussions.There are more questions and certainly a need to increase the critical pressure around why holography could be one of the most significant ways of seeing and representing worlds and ideas today. We are surrounded by terrible art (painting, sculpture, print, photography, performance, digital, moving image), and holography has undoubtedly contributed to the visual flotsam clogging our vision. This publication aims to identify the importance of critical conversation, and the place holography holds within our current and complex media landscape.